Self-Care Experience of Glaucoma Patients With Complications: A Phenomenological Study of Patients At Smec Manado Eye Clinic - Amelia Olii; Eko Winarto; Ns. Sonhaji (Jurnal Ners, 2026)
Glaucoma with complications is the second leading cause of blindness worldwide, with an estimated 60.5 million sufferers in 2010 increasing to 79.6 million in 2020, 47% of whom are in Asia, mainly due to Primary Angle-Closure Glaucoma (PACG). In Indonesia, the prevalence is around 4-5 per 1,000 population, with a significant increase in hospital visits from 65,774 in 2021 to 427,091 in 2022, indicating a lack of early awareness of this disease that can lead to permanent blindness, where early diagnosis and early treatment are crucial (Indonesia, 2023). This study aims to explore and understand the self-care experiences of patients with glaucoma complications using the Orem approach. This study uses a qualitative interpretative phenomenological method to explore the subjective experiences of glaucoma with complications patients at the SMEC Eye Clinic. A combination of bracketing and purposive sampling, involving only those who agreed to be interviewed and met the selected inclusion criteria, resulted in a sample of twenty participants (14 glaucoma with complications patients, 5 families, and 1 physician). Braun & Clarke thematic analysis was used to identify themes critical to a holistic understanding of self-care from the perspective of glaucoma patients. Results indicate that glaucoma with complications patients demonstrate a strong understanding of self-care but face significant external barriers. Limited local facilities force them to travel to other cities, leading to financial and psychological stressors such as depression and disappointment. Post-operative symptoms such as eye pain, a gritty feeling, blurred vision, and sensitivity to light also persist. However, they use positive coping mechanisms, such as managing emotions and praying, to overcome these challenges. In conclusion, the lived experience of glaucoma with complications patients is a complex struggle involving strong personal commitments, profound psychological challenges, and external systemic barriers that require comprehensive support from families and a more accessible healthcare system. Keywords: complications; glaucoma with complications patients; self care experience